Taxonomic changes in the gut microbiota are associated with cartilage damage independent of adiposity, high fat diet, and joint injury - Kelsey H. Collins (Nature Portfolio, 2021)
Abstract Lipodystrophic mice are protected from cartilage damage following joint injury. This protection can be reversed by the implantation of a small adipose tissue graft. The purpose of this study was to evaluate the relationship between the gut microbiota and knee cartilage damage while controlling for adiposity, high fat diet, and joint injury using lipodystrophic (LD) mice. LD and littermate control (WT) mice were fed a high fat diet, chow diet, or were rescued with fat implantation, then challenged with destabilization of the medial meniscus surgery to induce osteoarthritis (OA). 16S rRNA sequencing was conducted on feces. MaAslin2 was used to determine associations between taxonomic relative abundance and OA severity. While serum LPS levels between groups were similar, synovial fluid LPS levels were increased in both limbs of HFD WT mice compared to all groups, except for fat transplanted animals. The Bacteroidetes:Firmicutes ratio of the gut microbiota was significantly reduced in HFD and OA-rescued animals when compared to chow. Nine novel significant associations were found between gut microbiota taxa and OA severity. These findings suggest the presence of causal relationships the gut microbiome and cartilage health, independent of diet or adiposity, providing potential therapeutic targets through manipulation of the microbiome.